Peculiarities of Forecasting Competitiveness of Innovations for Industrial Enterprises - Sekerin, Vladimir Dmitrievich; Burlakov, Vyacheslav Viktorovich; Dzyurdzya, Olesya Anatolievna; Gorohova, Anna Evgenevna (International Journal of Economics and Financial Issues, 2015)
This article considers peculiarities of forecasting competitiveness of innovations for industrial enterprises. The theme of the article is urgent, because under conditions of economic crisis the competitiveness of industrial enterprises and thus their success on the market in many, if not in all, respects depend on the implemented innovations. The latter ensure a decrease in expenses, improvement of the quality, and growth of the workforce productivity at the enterprise. In their turn, innovations are the subject of demand on the part of industrial enterprises, and form the market of innovations that like any other market is characterized by demand, supply, and competition. That’s why it is not strange that the guarantee of successful commercialization of innovations is their own competitiveness that is made of the price and quality of the innovation. The goal of this work was to reveal the peculiarities of forecasting competitiveness of innovations for industrial enterprises and to offer recommendations on increasing the efficiency of forecasting. As a result of the conducted research, we have received the following essential inclusions: the innovation will be competitive in case of the availability of a reasonable innovation, stable demand, possibility to receive effect, and additional result that can occur as a result of implementing the innovation. Forecasting competitiveness of innovations of higher degrees must lead to the development of new methods of forecasting and, above all, methods of qualitative character that will supplement the methods and approaches that currently exist. Keywords: innovations, competitiveness, industrial enterprises, forecasting. JEL Classifications: L11; L15; L16; O14; O33